الجملة في كتاب الأربعين النووية عند نظرية محمد ابراهيم عبادة (دراسة نحوية): Sentences in the Book of al-Arba'in al-Nawawiyyah from the Perspective of Muhammad Ibrahim Ubadah's Theory (Syntactic Study) - Khairuyyasir, Azwar; Akmaliyah, Akmaliyah; Siti Muslikah; Mohammad Rosyid Ridho (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2025)
This study aims to identify the types and forms of sentences in Arabic language from the perspective of Muhammad Ibrahim Ubadah's theory, with the object of study being the book of Al-Arba’in Al-Nawawiyyah. The approach used is a syntactic approach. This study is a descriptive-qualitative research. The type of data used is qualitative data, and the source of data is the book of Al-Arba’in Al-Nawawiyyah. The data collection technique used is the observation-note method, and the analysis technique used is the distributive method, specifically BUL technique (Immediate Constituent Analysis). The results of this study show that there are six relevant types of sentences, including simple sentences, extended sentences, compound and complex sentences, complex sentences, embedded sentences, and intertwined sentences. From these sentence types, there are two forms in simple sentences, namely nominal and verbal patterns, five expansion forms in extended sentences, three connector forms in compound and complex sentences, five subordinating conjunction forms in complex sentences, two sentences that form embedded sentence patterns, and four sentences in intertwined sentence patterns. Through this study, it is expected to provide theoretical benefits and can be used as literature in the study of Arabic language.